2012
DOI: 10.1017/s0022377812000578
|View full text |Cite
|
Sign up to set email alerts
|

Dust-ion-acoustic solitary waves in a dusty plasma with arbitrarily charged dust and non-thermal electrons

Abstract: The dust-ion-acoustic solitary waves (DIA SWs) in an unmagnetized dusty plasma containing non-thermal electrons, cold mobile positive ions, and stationary arbitrarily (positively and negatively) charged static dust have been theoretically studied. The reductive perturbation technique has been employed to derive the Korteweg-de Vries equation, which admits SW solutions under certain conditions. It has been also shown that the basic features (amplitude, width, speed, etc.) of DIA SWs are significantly modified b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Figure 1(b) shows that the phase velocity of both the fast and slow waves is higher in the presence of negatively charged dust particles than the electron ion plasma case and less in the presence of positively charged dust particles. This increase in the phase velocity in the presence of negatively charged dust particles is due to the depletion of electron density in the background plasma which enlarge the electron Debye radius, i.e., there appears to be a stronger space charge electric field, which is responsible for the enhanced phase velocity of DIA waves (Kundu and Mamun 2012). Figure 1(c) indicates that with the increase of the negatively charged dust concentration, the phase velocity of both the fast and slow modes increases.…”
Section: Parametric Investigation Of Dispersion Relationmentioning
confidence: 99%
“…Figure 1(b) shows that the phase velocity of both the fast and slow waves is higher in the presence of negatively charged dust particles than the electron ion plasma case and less in the presence of positively charged dust particles. This increase in the phase velocity in the presence of negatively charged dust particles is due to the depletion of electron density in the background plasma which enlarge the electron Debye radius, i.e., there appears to be a stronger space charge electric field, which is responsible for the enhanced phase velocity of DIA waves (Kundu and Mamun 2012). Figure 1(c) indicates that with the increase of the negatively charged dust concentration, the phase velocity of both the fast and slow modes increases.…”
Section: Parametric Investigation Of Dispersion Relationmentioning
confidence: 99%
“…They have derived mK-dV equations and found only positive potential due to trapped electrons. Kundu and Mamun have considered three components unmagnetized dusty plasma and studied the nonlinear propagation of DIA solitary waves with arbitrarily charged stationary dust and non-thermaly distributed electrons [18]. They have shown that the DIA waves can support solitary structures associated with both positive and negative potential due to the presence of non-thermal electrons in their dusty plasma model.…”
Section: Introductionmentioning
confidence: 99%
“…1992). Therefore with dust as a stationary background, dust charge may be constant (Kundu & Mamun 2012) and so it is ‘dust ion acoustic’. In dust acoustic solitons with mobile dust, variable dust charges are being considered although it is questionable for conservation of mass.…”
Section: Introductionmentioning
confidence: 99%
“…Kopnin et al (2005) have pointed out that the dust grain charging process is described in terms of the so-called orbit motion (Barnes et al 1992). Therefore with dust as a stationary background, dust charge may be constant (Kundu & Mamun 2012) and so it is 'dust ion acoustic'. In dust acoustic solitons with mobile dust, variable dust charges are being considered although it is questionable for conservation of mass.…”
Section: Introductionmentioning
confidence: 99%